What does karl polanyi offer to economic theory - Grdešić, M. (Ekonomski Pregled, 2017)
This article provides a critical overview of the theoretical perspective developed by Karl Polanyi, in particular his 1944 book The Great Transformation. What does this approach offer to economic theory, especially heterodox economic theory? Three elements vital to his work are in focus: (1) “embeddedness” of the market in society, (2) fictitious commodities (labor, nature and money) and (3) the “double movement”, i.e. the political imposition of the self-regulating market and the protective reaction of society. The springboard for this article is a survey of American economists, in which they were asked if they had read Polanyi’s work. © 2017, Hrvatsko Drustvo Ekonomista. All rights reserved.
Keywords: double movement; economic theory; embeddedness; fictitious commodities; heterodox economics

Društvo I (ili) Tržište -- Sociološka Konceptualizacija Procesa Marketizacije Društva - Peračković, Krešimir (Gesellschaft und (oder) Markt. Eine soziologische Konzeptualisierung des Prozesses der Gesellschaftsmarketisierung., 2008)
The main goal of this work was to theoretically conceptualise the process of marketisation which designates the transformation of society into a market economy and social relations into market relations. The starting point is first the comparative analysis of the definitions of the term market by some classic authors (Smith, Marx, Weber, Durkheim and Parsons), each of whom define it from their perspective as a monetary mechanism of exchange in the economic sphere of social activity. In the second chapter K. Polanyi's theory of social transformation is presented, in which he is the first to state that the principle of market self-regulation has become the fundamental feature of modern society. Analysed in the third chapter is the market economy society model of D. Slater and F. Tonkiss, who claim that the process of marketisation in the most developed countries has already been completed and that today's society has already become a market society. The paper also presents in short the theory of marketing neglected in sociological literature, the main concept of market economy as a rational system of research and planning, which is currently not only applied in the economy but also in politics and culture. A special chapter is devoted to commodification, a process that concretises on a micro level the goals of marketisation, implying the transformation of nature, things, people, relations, meanings and immaterial resources into market commodities. The ultimate result of the marketisation and commmodification processes in a market society becomes evident in Rifkin's ominous hypothesis that all human life has become an experience to pay for, which is also the topic of the last chapter. (English)
Keywords: Kommodifizierung; Marketisierung; Markt; Marktgesellschaft; Marktverhältnisse; capitalism; commodification; comparative studies; definitions; komodifikacija; market; market relations; market society; marketing; marketisation; marketizacija; research; socioeconomics; tržišni odnosi; tržišno društvo; tržište

Postoji Li Mogućnost Instaliranja Socijalnog Kapitalizma U Post-Socijalističkoj Tranziciji? - Lošonc, Alpar (Is It Possible to Install Social Capitalism in Postsocialist Transition?, 2007)
Recently Claus Offe has raised the question concerning the fate of the European model of social capitalism. Can the model of social capitalism survive European integration amongst current tendencies? Offe assumes that this model has been challenged by the processes of globalisation and by the integration of postsocialist countries into the European Union. The working hypotheses of this article is that a relatively coherent answer to this question may be offered. The article is divided into three parts. The first part starts with Polanyi's socio-economic theory and emphasizes the importance of this approach for analyzing tendencies of capitalism in Western Europe and in post-socialist countries. The author argues that Polanyi's theory enables us to explain the forms of embedded liberalism in Western Europe after 1945, as well as the orientation of non-embedded neoliberalism and the functioning of the workfare state after the crisis of the Keynesian welfare state. The central element of social capitalism, namely, the welfare-state, despite globalizing tendencies projected by neoliberalism, still has dimensions of continuity. In the second section it is argued that an asymmetrical structure has arisen between Western Europe and the non-Western part of Europe concerning the socialisation of capitalism. Neoliberalisation in accordance with the model of transferring ideal-type capitalism is much more strongly implemented in transition countries. In the third part the author pleads for a broadening of the meaning of welfare to take into account the ecological aspect of welfare in countries in transition. The author insists that embeddedness must also include socio-ecological aspects of transition processes in postsocialist countries. Moreover, this theoretical approach provides an opportunity to explain the failures in implementing neoliberalism in postsocialist countries. If we introduce socio-ecological aspects we are in a much better position to answer Offe's question. (English)
Keywords: Europe; OFFE, Claus; capitalism; država blagostanja; neoliberalism; social anthropology; social capitalism; social psychology; socijalni kapitalizam; socio-ecological embeddedness; socio-ekološka utkanost; transition; tranzicija; welfare state